2014
DOI: 10.5194/hess-18-5001-2014
|View full text |Cite
|
Sign up to set email alerts
|

Building a field- and model-based climatology of local water and energy cycles in the cultivated Sahel – annual budgets and seasonality

Abstract: Abstract. In the sub-Saharan Sahel, energy and water cycling at the land surface is pivotal for the regional climate, water resources and land productivity, yet it is still very poorly documented. As a step towards a comprehensive climatological description of surface fluxes in this area, this study provides estimates of long-term average annual budgets and seasonal cycles for two main land use types of the cultivated Sahelian belt: rainfed millet crop and fallow bush. These estimates build on the combination … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
44
0
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(50 citation statements)
references
References 81 publications
4
44
0
2
Order By: Relevance
“…Merbold et al [22] found that mean annual rainfall is strongly correlated with maximum photosynthetic capacity and is the predominant factor driving C fluxes across Africa. With rainfall, the greening phase commences (Figure 2), and soil moisture is replenished, which impacts the amount of energy partitioned into evapotranspiration [21,23,24]. Rainfall also increases humidity, which lowers the difference between the vapor pressure deficit inside the leaf and that of the air.…”
Section: Introductionmentioning
confidence: 99%
“…Merbold et al [22] found that mean annual rainfall is strongly correlated with maximum photosynthetic capacity and is the predominant factor driving C fluxes across Africa. With rainfall, the greening phase commences (Figure 2), and soil moisture is replenished, which impacts the amount of energy partitioned into evapotranspiration [21,23,24]. Rainfall also increases humidity, which lowers the difference between the vapor pressure deficit inside the leaf and that of the air.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, a SEB model driven by MSG SEVIRI and MODIS observations in conjunction with an aggregation scheme is used to estimate H and LE over a transect of about 3.2 km located at the Wankama Catchment (Niger) [24][25][26][27][28][29]. A spatial aggregation approach is conceived as a method which seeks to link the model parameters that control surface exchange (Ts, α, d, z_0, LAI, and hc) on a patch scale with the area-average value of equivalent model parameters applicable on a larger scale or grid-scale, assuming that the same equations are used to describe surface fluxes at both scales [27,[30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…These land covers are representative of the surrounding region and capture the range from more to less anthropogenic land uses. The multi-use comparison over multiple seasonal cycles puts this study among the few recent, long-term studies in this region (Bagayoko et al, 2007;Brümmer et al, 2008;Ezzahar et al, 2009;Guichard et al, 2009;Guyot et al, 2009, Lohou et al, 2010Mamadou et al, 2014Mamadou et al, , 2016Mauder et al, 2006;Ramier et al, 2009;Timouk et al, 2009;Velluet et al, 2014). We calculate the evaporative fraction over the study period and compare it with land cover and atmospheric controls, in order to provide estimation based on the physical basis of fluxes.…”
Section: Introductionmentioning
confidence: 99%